Management of the introduction of innovations in the company's activities - Liu Jie (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the innovative activity of organizations. The subject of research includes the theoretical and applied aspects of managing the innovative activities of enterprises in modern conditions. The purpose of the master's thesis is to provide scientific substantiation of theoretical and methodological approaches to managing the innovative activities of organizations and to develop practical recommendations for stimulating the innovative potential of enterprises. he results obtained are of practical significance, as the main conclusions and provisions of the study are presented in the form of actionable recommendations aimed at intensifying the development of innovative activities in enterprises. These recommendations are intended to contribute to the recovery and growth of Ukraine's economy. This study underscores the critical role of innovation in driving economic recovery and competitiveness in Ukraine. By addressing both theoretical and practical aspects, it offers a comprehensive roadmap for enterprises to enhance their innovative potential and adapt to modern challenges.
Scientific advisor: Chkheailo A., PhD in philosophy, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; innovative activities; banking innovations; benchmarking; innovation clusters; benchmarking